Nano-Pr2O3 Doped PVA + Na3C6H5O7 Polymer Electrolyte Films for Electrochemical Cell Applications - J. Ramesh Babu; K. Ravindhranath; K. Vijaya Kumar (International Journal of Polymer Science)
Varying concentrations of nano-Pr2O3 doped in “PVA + Sodium Citrate (90 : 10)” polyelectrolyte films are synthesized using solution cast technique and the films are characterized adopting FTIR, XRD, SEM, and DSC methods. The film with 3.0% of nano-Pr2O3 content is more homogenous and possesses more amorphous region that facilitate the deeper penetration of nanoparticles into the film causing more interactions between the functional groups of the polymeric film and nano-Pr2O3 particles and thereby turning the film more friendlily to the proton conductivity. The conductivity is maximum of 7 × 10−4 S/cm at room temperature for 3.0% nano-Pr2O3 film and at that composition, the activation energy and crystallinity are low. With increase in temperature, the conductivity is increasing and it is attributed to the hopping of interchain and intrachain ion movements and furthermore decrease in microscopic viscosity of the films. The major charge carriers are ions and not electrons. These films are incorporated successfully as polyelectrolytes in electrochemical cells which are evaluated for their discharge characteristics. It is found that the discharge time is maximum of 140 hrs with open circuit voltage of 1.78 V for film containing 3% of nano-Pr2O3 and this reflects its adoptability in the solid-state battery applications.